2013
DOI: 10.1177/1071100713495380
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Dorsiflexion Arthrodesis to Salvage Chopart’s Amputation With Anterior Skin Insufficiency

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…A lot of factors are involved in the decision; vascularity, presence of infection and its level, availability of enough tissue for coverage, patient's age, general health, life expectancy, other co-morbidities and the patients' choice and emotional wellbeing. 9 Complex cases involving unsalvageable forefoot make some surgeons choose the safest operation with the highest success rate neglecting the energy expenditure leading to smaller healthy residual stump in patients who can't mobilize. 10 Moreover HRQoL is a critical indicator of overall patient health; and using The RAND 36 questionnaires in this study showed significant difference between the modified Chopart's and BKA group in the physical function, emotional role limitation and social function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of factors are involved in the decision; vascularity, presence of infection and its level, availability of enough tissue for coverage, patient's age, general health, life expectancy, other co-morbidities and the patients' choice and emotional wellbeing. 9 Complex cases involving unsalvageable forefoot make some surgeons choose the safest operation with the highest success rate neglecting the energy expenditure leading to smaller healthy residual stump in patients who can't mobilize. 10 Moreover HRQoL is a critical indicator of overall patient health; and using The RAND 36 questionnaires in this study showed significant difference between the modified Chopart's and BKA group in the physical function, emotional role limitation and social function.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Krause and colleagues we only included patients that had wounds that can only be closed primary while patients considered for free flap coverage were excluded from this study. 9 We used arthrodesis in 2 cases of plantar ulcers complicating equinovarus deformity.…”
Section: Discussionmentioning
confidence: 99%
“…3 Unfortunately, subjects with CA are prone to developing a severe hindfoot equinus over time due to muscular imbalance of the tibia-gastroc-soleus complex caused either by a developing weakness of dorsiflexors or by dorsiflexors that were not restored during surgery. 4 In addition, the decrease in foot length results in a loss of the biomechanical fore foot lever, leading to a complete loss of the ability to push off in late stance. 5 In order to improve standing and walking in these individuals, a prosthetic device is mandatory to restore the lost biomechanical leverage.…”
Section: Introductionmentioning
confidence: 99%
“…The instrumented five-step staircase (height: 16 cm; depth: 27 cm; width: 100 cm) with handrails on each side. The left side(2,4,6) and the right side(1,3,5) are placed on one force plate each.…”
mentioning
confidence: 99%
“… 5 In severe cases in which stump coverage with soft tissue has failed, the decision to give up preservation of the heel and perform a higher level leg amputation may be made. 4 , 6 , 7 We report a case of postoperative extensive necrosis of the tissue covering the stump after Chopart’s amputation of an injured foot. It was successfully treated by secondary stump reconstruction with the combined use of an artificial dermis and anterolateral thigh (ALT) flap.…”
mentioning
confidence: 99%